2015
DOI: 10.1177/0164027515622244
|View full text |Cite
|
Sign up to set email alerts
|

Rebalance Without the Balance: A Research Note on the Availability of Community-Based Services in Areas Where Nursing Homes Have Closed

Abstract: Policies to “rebalance” funding away from nursing homes and toward home and community-based services (HCBS) have encouraged national trends of nursing home closure and an expansion of the HCBS industry. These changes are unfolding without a clear understanding of what services are available at the local level. The purpose of this study was: (1) to describe the current distribution of community-based services (CBS) in areas where nursing homes have closed and (2) to examine differences in availability of CBS us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Problems in the rural health care and LTSS systems are longstanding and well-known to rural stakeholders. In addition to the familiar challenge of sustaining services in rural, low-volume settings (Medicare Payment Advisory Commission, 2008), notable weaknesses in the rural LTSS infrastructure include shortages of primary care professionals (Doescher, Skillman, & Rosenblatt, 2009), difficulties in recruiting and retaining direct service workers (D. K. Brown, Lash, Wright, & Tomisek, 2011), and a scarcity of HCBS provider organizations (Coburn et al, 2006;Hawes, Sherman, Hutchison, Phillips, & Holan, 2005;Hong, 2006;Melnick, Ferrer, Shanks-McElroy, & Dunay, 2013;Tyler & Fennell, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Problems in the rural health care and LTSS systems are longstanding and well-known to rural stakeholders. In addition to the familiar challenge of sustaining services in rural, low-volume settings (Medicare Payment Advisory Commission, 2008), notable weaknesses in the rural LTSS infrastructure include shortages of primary care professionals (Doescher, Skillman, & Rosenblatt, 2009), difficulties in recruiting and retaining direct service workers (D. K. Brown, Lash, Wright, & Tomisek, 2011), and a scarcity of HCBS provider organizations (Coburn et al, 2006;Hawes, Sherman, Hutchison, Phillips, & Holan, 2005;Hong, 2006;Melnick, Ferrer, Shanks-McElroy, & Dunay, 2013;Tyler & Fennell, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the availability of HCBS (Coburn et al, 2006) and residential care (Lenardson et al, 2014) have been thought to be more limited, though much of the data on these questions are dated. However, in a recent national study of services in markets where nursing homes have closed, Tyler and Fennell (2017) found rural areas lacked community-based services in comparison with urban markets. Moreover, family caregiving may be growing less available in rural areas, as more working-age adults leave rural communities for job opportunities elsewhere (Nash, Tramuto, & Coughlin, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that rebalancing efforts may have unintended consequences. Groups may not benefit equally 3,16 from policy interventions such as BIP if there are barriers to the existence or growth of HCBS. Further, policies emphasizing HCBS over institutional LTSS may have unintended negative effects on rural persons by limiting the institutional LTSS safety net.…”
Section: Conclusion and Relevancementioning
confidence: 99%
“…3 Additionally, recent analyses found that in rural areas, nursing home closures occurred despite limited availability of HCBS services in their stead. 16 Medical care access disparities have been attributed to structural factors, such as limited transportation infrastructure, distances separating providers and patients, and provider shortages. 15,[17][18][19] In tandem with these medical care barriers, rural populations tend to be older, poorer, and fare worse on numerous health indicators compared to urban residents.…”
Section: Introductionmentioning
confidence: 99%